FIELD AND STRUCTURAL GEOLOGY OF THE DUNGULBI AREA, NORTHEASTERN NIGERIA - Rufai, Fauziya Ahmed; Halilu, Maimuna; Abba Ahmed, Hafizullah.; Ghani, Shamsuddeen S. (IJRDO-Journal of Applied Science, 2017)
Basement rocks of the Dungulbi area of Northeastern Nigeria were assessed and found tocomprise of Pre-Cambrian basement rocks invaded by Pan-African granites generally referredto as the ‘Older Granites’. The area was composed mainly of Migmatite gneiss, granite gneissesand calc-alkaline granites. The tectonic structures in the study area trend mostly NE – SW andsubordinately NW-SE and N-S conform with the regional deformational structures whichoccurred during the Pan African thermotectonic events in the Nigerian basement.